Petrodensity map of the Precambrian basement of the Voronezh crystalline massif (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: The article presents a petrodensity map of the Precambrian basement of the Voronezh crystalline massif (scale of 1: 1,000,000) together with an explanatory note, published in July 2020 by the Scientific World publishing house. A CD with all the materials collected by the authors is provided together with the map. Methodology: The map was designed by a team of researchers from the Faculty of Geology of Voronezh State University, including Glaznev V. N., Muravina O. M., Zhavoronkin V. I., Lebedev I. P., and Voronova T. A. The map is the result of many years of work on the generalization and analysis of data on the density properties of the structural and compositional complexes of the Precambrian basement of the Voronezh crystalline massif. Results and Discussion: The explanatory note describes the density properties of the structural and compositional geological complexes of the Precambrian basement of the Voronezh crystalline massif located in the central part of the East European Platform. It also provides general information about the previous studies of the basement rocks, their geology, and tectonics. The characteristics of the sedimentary cover are given. The note also provides a systematic description of the density properties of the basement rocks in the studied area and describes the regularities of relationships between the petrophysical characteristics of the rocks and the observed geophysical fields, as well as the correlation between the density values and other petrophysical properties. Conclusions: An effective model of the density of the crystalline basement of the Voronezh massif enables new interpretations of the gravity anomalies and the construction of three-dimensional density models of the region at various scales. The map and the explanatory note can be used as a teaching aid for specific sections of the course in petrophysics and interpretation of potential fields included in the master's and graduate degree programmes. The emphasis on the practical applications of the petrodensity data means that it can be of interest to geophysicists and geologists employed at industrial enterprises.
Keywords: petrodensity map; Voronezh crystalline massif; petrophysics; gravitational field